The Many Faces of Thin Basement Membrane Nephropathy; A Population Based Study - Kyriacou, Kyriacos; Nearchou, Marianna; Zouvani, Ioanna; Flouri, Christina; Loizidou, Maria; Hadjigavriel, Michael; Hadjisavvas, Andreas; Ioannou, Kyriacos (IntechOpen, 2012)
None